Asymmetrical four-wire cascaded h-bridge multi-level inverter based shunt active power filter supplied by a photovoltaic source - Kamel Saleh; Omar Mahmoud (Institute of Advanced Engineering and Science, 2021)
This paper presents a novel shunt active power filter (SAPF). The power converter that is used in this SAPF is constructed from a four-leg asymmetric multi-level cascaded H-bridge (CHB) inverter that is fed from a photovoltaic source. A three-dimensional space vector modulation (3D-SVPWM) technique is adopted in this work. The multi-level inverter can generate 27-level output with harmonic content is almost zero. In addition to the capability to inject reactive power and mitigating the harmonics, the proposed SAPF has also, the ability to inject real power as it is fed from a PV source. Moreover, it has a fault-tolerant capability that makes the SAPF maintaining its operation under a loss of one leg of the multi-level inverter due to an open-circuit fault without any degradation in the performance. The proposed SAPF is designed and simulated in MATLAB SIMULINK using a single nonlinear load and the results have shown a significant reduction in total harmonics distortion (THD) of the source current under the normal operating condition and post a failure in one phase of the SAPF. Also, similar results are obtained when IEEE 15 bus network is used.